インド洋および南極海における浮遊粒子状物質の化学組成に関する研究 - 中口, 譲; ナカグチ, ユズル; 廣田, 晶子; ヒロタ, アキコ (近畿大学理工学総合研究所, 2016)
[Abstract] The origin of particulate matter which collected from the Indian Ocean and the Antarctic Ocean was clarified by individual particle analysis. Iron-rich particle which carried from land was observed at the surface in all sampling stations. Aluminum-dominant and Al-Si particles were observed at ER-5, 8 and 10 in the Indian Ocean sampling stations. These results confirmed that these particles were land origin such as aluminosilicate. A lot of silica dominant particles were observed at ER-14 in the Antarctic Ocean station. The SEM image of these particulate matter suggested that these particles were originated from diatom. The number of biogenic particles which exist at the surface has decreased with increase of depth. application/pdf departmental bulletin paper